Population Pharmacokinetics of Vancomycin in Patients Undergoing Allogeneic Hematopoietic Stem‐Cell Transplantation. (15th May 2018) - Okada, Akira; Kariya, Misato; Irie, Kei; Okada, Yutaka; Hiramoto, Nobuhiro; Hashimoto, Hisako; Kajioka, Ryosuke; Maruyama, Chika; Kasai, Hidefumi; Hamori, Mami; Nishimura, Asako; Shibata, Nobuhito; et al.
Abstract: Vancomycin is a commonly used antimicrobial agent for patients undergoing allogeneic hematopoietic stem‐cell transplantation (allo‐HSCT). Vancomycin has large inter‐ and intraindividual pharmacokinetic variability, which is mainly described by renal function; various studies have indicated that vancomycin pharmacokinetics are altered in special populations. However, little is known regarding vancomycin pharmacokinetics in patients undergoing allo‐HSCT. Therefore, we aimed to develop a population pharmacokinetic (PopPK) model of vancomycin in patients undergoing allo‐HSCT for effective and safe antimicrobial therapy and to develop a vancomycin dosing nomogram for a vancomycin optimal‐dosing strategy. In total, 285 observations from 95 patients undergoing allo‐HSCT were available. The final PopPK parameter estimates were central volume of distribution (V1, L),  39.2; clearance (L/h),  4.25; peripheral volume of distribution (V2, L), 56.1; and intercompartmental clearance (L/h),  1.95. The developed vancomycin model revealed an increase in V1 and V2 compared with those in the general population that consisted of patients with methicillin‐resistant Staphylococcus aureus . Moreover, serum creatinine was reduced because of an increase in the plasma fraction because of destruction of hematopoietic stem cells accompanying allo‐HSCT pretreatment, suggesting that the Cockcroft–Gault equation–based creatinine clearance value was overestimated. To our knowledge, this is the first PopPK study to develop a dosing nomogram for vancomycin in patients undergoing allo‐HSCT and was proven to be useful in optimizing the dosage and dosing interval of vancomycin in these patients. This strategy will provide more useful information for vancomycin therapy with an evidence‐based dose adjustment.